A [NOON] tetradentate ligand fourth subgroup metal complex, a catalyst for olefin polymerization and a method for preparing polyolefin

By using the [NOON]tetradentate ligand fourth subgroup metal complex as the main catalyst, a catalyst for olefin polymerization with high activity and controllable structure is prepared, which solves the problems of poor catalytic life and low copolymerization insertion rate in the existing technology. problem, realizing polyolefin elastomers with high molecular weight and high copolymerization insertion rate.

CN117986290BActive Publication Date: 2025-01-24BEOYI (SHANDONG) NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410130407.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-29
Publication Date
2025-01-24
Estimated Expiration
2044-01-29

AI Technical Summary

Technical Problem

In the prior art, the catalytic life of the ethylene and α-olefin copolymerization catalyst is poor, the thermal stability and copolymerization insertion rate are low, making it difficult to achieve polyolefin elastomers with high molecular weight and copolymerization insertion rate.

Method used

The [Noon] four -tooth ligand fourth -associated metal mathematical object is used as the main catalyst, and a highly active and structural controlled olefin polymerization catalyst is prepared through specific synthetic routes and process conditions.

Benefits of technology

The polyolefin elastic body with high molecular weight and high club interpolation rate is achieved, the controllability of catalytic activity and polymer structure is improved, and the life of the catalyst is prolonged.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004689817590000021
    Figure BDA0004689817590000021
  • Figure BDA0004689817590000031
    Figure BDA0004689817590000031
  • Figure BDA0004689817590000041
    Figure BDA0004689817590000041
Patent Text Reader

Abstract

The present invention relates to the technical field of olefin polymerization catalysts, specifically a [NOON] tetradentate ligand fourth subgroup metal complex, a catalyst for olefin polymerization and a method for preparing polyolefin. The complex provided by the present invention is used to catalyze the polymerization of ethylene and / or alpha-olefins to obtain a polyolefin elastomer with a high molecular weight and a high copolymerization insertion rate. The catalyst for olefin polymerization provided by the present invention is based on the complex as a main catalyst, has high catalytic activity and polymer structure controllability, and has a low amount of co-catalyst, and can be highly active by optimizing catalyst substitution groups and polymerization conditions. Catalysts for the copolymerization of ethylene and alpha-olefins can be prepared to prepare polyolefin elastomers (POE). In the experiment of the present invention, a catalyst for olefin polymerization using the [NOON] tetradentate ligand fourth subgroup metal complex as a main catalyst of the present invention is used to prepare polyolefins, and its insertion rate is as high as 11.5mol%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of olefin polymerization catalysts, in particular to a [NOON] tetradentate ligand fourth subgroup metal complex, an olefin polymerization catalyst and a method for preparing polyolefin. Background Art

[0002] Polyolefin materials, such as polyethylene, polypropylene and ethylene / α-olefin copolymers, have many excellent properties, such as good chemical stability, corrosion resistance, harmlessness and low cost. In current industrial production, polyolefin products account for a large proportion. For example, polyolefin elastomer (POE) is a thermoplastic elastomer produced by copolymerization of ethylene and α-olefin, in which the crystalline region of the polyethylene chain (resin phase) acts as a physical crosslinking point and has typical plastic properties. After adding a certain amount of α-olefin (1-butene, 1-hexene, 1-octene, etc.), the crystalline region of the polyethylene chain is weakened, forming an amorphous region (rubber phase) showing rubber elasticity, so that the product has the properties of an elastomer. POE has the dual characteristics of plastics and rubbers and has excellent comprehensive performance, so POE can be regarded as a bridge product between plastics and rubbers.

[0003] The development of new polyolefin materials is closely related to the innovation of catalysts. The emergence of ZN catalysts has enabled the widespread production and application of polyethylene and polypropylene. The emergence of methylaluminoxane (MAO) in the 1980s enabled the application of metallocene catalysts in the industrial production of polyolefins. However, the preparation process of metallocene catalysts is harsh, resulting in high production costs of metallocene polyolefins. Lower-cost non-metallocene catalysts have become a hot topic in polyolefin catalyst research in recent years.

[0004] The non-cyclopentadienyl tridentate binuclear titanium catalyst patent invented in CN201410393654.5 can catalyze ethylene polymerization and copolymerization of ethylene and α-olefins with high activity under the activation of MMAO to obtain polymers with relatively high Mw and relatively narrow MWD, but the catalytic life of this catalyst is poor.

[0005] A modified high-efficiency Ziegler-Natta catalyst provided by CN101885793A can catalyze the polymerization of ethylene and α-olefins, but this type of catalyst has poor thermal stability and a low insertion rate in the copolymerization of ethylene and α-olefins. Therefore, it is necessary to continue to develop new non-metallocene catalysts to improve polymerization activity and achieve controllable production of polymer structures. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a [NOON] tetradentate ligand fourth subgroup metal complex, an olefin polymerization catalyst and a method for preparing polyolefin. The [NOON] tetradentate ligand fourth subgroup metal complex provided by the present invention is used to catalyze the polymerization of ethylene and / or α-olefin to obtain a polyolefin elastomer with a high molecular weight and a high copolymerization insertion rate.

[0007] The present invention provides a [NOON] tetradentate ligand fourth subgroup metal complex having a structure of formula (I):

[0008]

[0009] Wherein, R1, R2 and R3 are independently hydrogen, halogen, C1-C 20 Alkyl, C1~C 20 Cycloalkyl, C1~C 10 Alkoxy, C1~C 10 Perfluoroalkyl, phenyl or substituted phenyl;

[0010] Said X is halogen, methyl or benzyl;

[0011] The M is a fourth subgroup transition metal.

[0012] Preferably, R1 and R2 of the present invention are independently hydrogen, fluorine, chlorine, methyl, methoxy, trifluoromethyl, isopropyl, tert-butyl, phenyl, 3,5-dimethylphenyl or 3,5-di-tert-butylphenyl; R3 is hydrogen, methyl, ethyl, isopropyl, tert-butyl, cyclohexyl or phenyl. In certain embodiments of the present invention, R1 and R2 are independently hydrogen, methyl or tert-butyl; R3 is hydrogen, methyl, ethyl, isopropyl or cyclohexyl. Preferably, X of the present invention is chlorine, bromine or methyl. In certain embodiments of the present invention, X is chlorine or methyl. Preferably, M of the present invention is titanium, zirconium or hafnium.

[0013] In certain embodiments of the present invention, the complex having the structure of formula (I) is specifically a complex having the structures shown in the following F1 to F10:

[0014] F1: R1 = hydrogen, R2 = hydrogen, R3 = methyl, M = Ti, X = methyl;

[0015] F2: R1 = hydrogen, R2 = methyl, R3 = ethyl, M = Ti, X = Cl;

[0016] F3: R1 = methyl, R2 = hydrogen, R3 = hydrogen, M = Zr, X = methyl;

[0017] F4: R1 = methyl, R2 = hydrogen, R3 = ethyl, M = Zr, X = methyl;

[0018] F5: R1 = tert-butyl, R2 = methyl, R3 = isopropyl, M = Zr, X = Cl;

[0019] F6: R1 = methyl, R2 = tert-butyl, R3 = cyclohexyl, M = Zr, X = methyl;

[0020] F7: R1 = methyl, R2 = hydrogen, R3 = isopropyl, M = Hf, X = methyl;

[0021] F8: R1 = methyl, R2 = hydrogen, R3 = ethyl, M = Hf, X = Cl;

[0022] F9: R1 = hydrogen, R2 = tert-butyl, R3 = cyclohexyl, M = Hf, X = methyl;

[0023] F10: R1 = methyl, R2 = methyl, R3 = cyclohexyl, M = Hf, X = Cl.

[0024] The present invention provides a method for preparing the above-mentioned [NOON] tetradentate ligand fourth subgroup metal complex, comprising the following steps:

[0025] S1) reacting the compound of formula A with CH3OCH2Cl to obtain a compound of formula B;

[0026]

[0027] Wherein, the R1 and R2 are the same as R1 and R2 in the aforementioned [NOON] tetradentate ligand fourth subgroup metal complex, and are not described in detail;

[0028] S2) reacting the compound represented by formula C with the compound represented by formula B obtained in step S1) to obtain a compound represented by formula D;

[0029]

[0030] Wherein, the R3 is the same as the R3 in the above-mentioned [NOON] tetradentate ligand fourth subgroup metal complex, and will not be described in detail;

[0031] S3) heating the compound of formula D obtained in step S2) under reflux to obtain a compound of formula E;

[0032]

[0033] S4) combining MG4 and the compound of formula E obtained in step S3) to obtain a compound of formula F;

[0034]

[0035] Among them, M in the MG4 is the same as M in the above-mentioned [NOON] tetradentate ligand fourth subgroup metal complex, which is not repeated here; G in the MG4 is a halogen, specifically chlorine or bromine; X in the compound of the structure shown in formula F is the same as X in the above-mentioned [NOON] tetradentate ligand fourth subgroup metal complex, which is not repeated here.

[0036] The present invention first reacts the compound of the structure shown in formula A with CH3OCH2Cl to obtain the compound of the structure shown in formula B; specifically, the present invention reacts the compound of the structure shown in formula A with a catalyst in a solvent under anhydrous and oxygen-free conditions, then adds CH3OCH2Cl thereto, and then successively filters, extracts and dries to obtain the compound of the structure shown in formula B. The temperature of the reaction of the present invention is room temperature, specifically 25°C, and the reaction time is 2h. In certain embodiments of the present invention, the reaction amount of the compound of the structure shown in formula A is 1.0 to 2.0 equivalents, preferably 1.0 equivalents; the reaction amount of CH3OCH2Cl is 1.0 to 2.5 equivalents, preferably 1.1 equivalents; the equivalent of the catalyst is 1.0 to 2.0 equivalents, preferably 1.1 equivalents. In certain embodiments of the present invention, the catalyst is NaH and the solvent is THF.

[0037] After obtaining the compound of the structure shown in formula B, the compound of the structure shown in formula C and the obtained compound of the structure shown in formula B are reacted to obtain a compound of the structure shown in formula D. Specifically, under a protective gas atmosphere, the compound of the structure shown in formula C and the obtained compound of the structure shown in formula B are reacted in a solvent, and then dried and recrystallized in sequence to obtain a compound of the structure shown in formula D. The reaction amount of the compound of the structure shown in formula C of the present invention is 1.0 to 1.5 equivalents, preferably 1.1 equivalents. The reaction amount of the compound of the structure shown in formula B of the present invention is 2.0 equivalents. The temperature of the reaction of the present invention is room temperature, and the room temperature is the same as above and will not be repeated; the reaction time is 2h. In certain embodiments of the present invention, the protective gas of the present invention is nitrogen; the solvent is THF.

[0038] After obtaining the compound of the structure shown in formula D, the compound of the structure shown in formula D is subjected to heating reflux reaction to obtain the compound of the structure shown in formula E. Specifically, the compound of the structure shown in formula D and hydrochloric acid are subjected to heating reflux reaction in a solvent, and then dried and recrystallized in sequence to obtain the compound of the structure shown in formula E. The reaction amount of the compound of the structure shown in formula D of the present invention is 1.0 equivalent. The reaction amount of hydrochloric acid of the present invention is 6.0 equivalents. The temperature of the heating reflux reaction of the present invention is 120° C., and the time is 3 hours.

[0039] After obtaining the compound of the structure shown in Formula E, the present invention further comprises MG4 and the obtained compound of the structure shown in Formula E to obtain the compound of the structure shown in Formula F. Specifically, under anhydrous and oxygen-free conditions, MG4 and the obtained compound of the structure shown in Formula E are dissolved in a solvent at low temperature, a Grignard reagent is added or not, and then reacted at room temperature for 1 hour to obtain a compound of the structure shown in Formula F. More specifically, if a Grignard reagent is added in the present invention, the reaction is first carried out at low temperature for 1 hour after the addition; the Grignard reagent is a methylated Grignard reagent, such as methyl magnesium bromide ethyl ether, or the Grignard reagent is a benzylated Grignard reagent, such as benzyl magnesium bromide. The reaction amount of MG4 in the present invention is 1.0 equivalent; the reaction amount of the compound of the structure shown in Formula E is 1.0 equivalent. If a Grignard reagent is added in the present invention, the reaction amount is 4.0 to 4.5 equivalents, preferably 4.4 equivalents. In certain embodiments of the present invention, the low temperature is -35°C; the room temperature is the same as above and will not be repeated. In certain embodiments of the present invention, the solvent is toluene.

[0040] The synthesis of the [NOON] tetradentate ligand fourth subgroup metal complex of the present invention is not limited to the aforementioned preparation method. Those skilled in the art can synthesize the [NOON] tetradentate ligand fourth subgroup metal complex by different methods based on existing chemical knowledge.

[0041] The present invention also provides a catalyst for olefin polymerization, which comprises a main catalyst and a co-catalyst; the main catalyst comprises the above-mentioned [NOON] tetradentate ligand fourth subgroup metal complex.

[0042] Specifically, the cocatalyst of the present invention is selected from one or more of modified or unmodified alkylaluminoxane, alkylaluminum, organic boron or organic borate. Preferably, the cocatalyst is selected from one or more of methylaluminoxane, modified methylaluminoxane, triethylaluminum, triisobutylaluminum, trioctylaluminum, perfluorophenylboron, triphenylcarbonium tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate and N,N-dioctadecylmethylammonium tetrakis(pentafluorophenyl)borate. In certain embodiments of the present invention, the molar ratio of the aluminum atoms in the cocatalyst, the boron atoms in the cocatalyst and the metal atoms in the main catalyst is (5-1000):0:1, or 0:(1-5):1, or (5-1000):(1-5):1; when the present invention uses a boron-containing cocatalyst, it is beneficial to remove impurities when used in combination with an aluminum-containing cocatalyst.

[0043] The present invention also provides a method for preparing polyolefin, comprising the following steps:

[0044] polymerizing at least one of ethylene or α-olefin under the action of a catalyst to obtain a polyolefin;

[0045] The catalyst is the same as the above-mentioned catalyst for olefin polymerization and will not be described in detail.

[0046] The polymerization of the present invention is specifically to homopolymerize ethylene under the action of a catalyst; or to homopolymerize α-olefin under the action of a catalyst; or to copolymerize ethylene and α-olefin under the action of a catalyst; the temperature of the homopolymerization or copolymerization is 50 to 150°C, and the homopolymerization or copolymerization is carried out at a pressure of 0.1 to 5MPa; the α-olefin is selected from one of propylene, 1-butene, 1-hexene, 1-octene and 1-decene. More specifically, the polymerization of the present invention is carried out in a saturated alkane; the saturated alkane is selected from one of n-pentane, n-hexane, cyclohexane, n-heptane, methylcyclohexane, n-octane and isooctane.

[0047] The preparation method of polyolefin provided by the present invention adopts a solution polymerization process to prepare the polymer, and n-pentane, n-hexane, cyclohexane, n-heptane, methylcyclohexane, n-octane, isooctane can be selected as solvents as needed. The present invention polymerizes at least one of ethylene or α-olefin under the action of a catalyst, and the polymerization temperature is 50 to 150°C, preferably 80 to 150°C, and more preferably 100 to 150°C; the present invention belongs to solution polymerization, and the polymerization is carried out at a pressure of 0.1 to 5MPa, preferably 1.5 to 5.0MPa, and more preferably 3.5 to 5.0MPa.

[0048] The present invention has a large difference in polymerization reaction time according to the different factors such as the catalyst used, the type and concentration of the monomer, and the reaction temperature. For the copolymerization of ethylene and 1-octene, 5 to 30 minutes are required. In certain embodiments of the present invention, the specific process of catalyzing the copolymerization of ethylene and 1-octene of the present invention is: in the presence of ethylene, add the comonomer, the main catalyst and the cocatalyst to the polymerization kettle, stir the reaction at 50 to 150 ° C for 5 to 30 minutes, and then add an appropriate amount of ethanol to terminate the copolymerization reaction. The temperature of the reaction system is lowered to room temperature, filtered, and vacuum dried to constant weight to obtain a polymer.

[0049] The present invention provides a [NOON] tetradentate ligand fourth sub-group metal complex, an olefin polymerization catalyst and a method for preparing polyolefin. The [NOON] tetradentate ligand fourth sub-group metal complex provided by the present invention is used to catalyze the polymerization of ethylene and / or α-olefin to obtain a polyolefin elastomer with a high molecular weight and a high copolymerization insertion rate. The olefin polymerization catalyst provided by the present invention uses the [NOON] tetradentate ligand fourth sub-group metal complex as a main catalyst, has high catalytic activity and polymer structure controllability, and has a low amount of co-catalyst. By optimizing the catalyst substitution group and polymerization conditions, it can catalyze the copolymerization of ethylene and α-olefin with high activity to prepare polyolefin elastomer (POE). In the experiment of the present invention, the olefin polymerization catalyst using the [NOON] tetradentate ligand fourth sub-group metal complex of the present invention as a main catalyst is used to prepare polyolefin, and its insertion rate is as high as 11.5 mol%. DETAILED DESCRIPTION

[0050] The present invention discloses a method for preparing a [NOON] tetradentate ligand fourth subgroup metal complex, a catalyst for olefin polymerization, and a polyolefin. A person skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the above. It should be particularly noted that all similar substitutions and modifications are obvious to a person skilled in the art and are considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.

[0051] The present invention provides a method for synthesizing a [NOON] tetradentate ligand fourth subgroup metal complex, and the specific synthesis route is as follows:

[0052]

[0053] The specific preparation process of the novel polyolefin elastomer catalyst of the present invention is as follows:

[0054] (1) General method for ligand synthesis

[0055] Under anhydrous and oxygen-free conditions, weigh 1.0-2.0 equivalents (preferably 1.0 equivalents) of compound A, add an appropriate amount of THF to fully dissolve, then add 1.0-2.0 equivalents (preferably 1.1 equivalents) of NaH, react at room temperature for 2 hours, add 1.0-2.5 equivalents of CH3OCH2Cl (preferably 1.1 equivalents), filter the obtained mixture, spin-dry the filtrate, add dichloromethane and water to extract, collect the organic phase, dry it over anhydrous magnesium sulfate, and spin-dry to obtain compound B.

[0056] Under nitrogen atmosphere, 2.0 equivalents of B were dissolved in an appropriate amount of THF, and then 1.0-1.5 equivalents (preferably 1.1 equivalents) of compound C were added. The reaction was allowed to react at room temperature for 3 h. The reaction solution was spin-dried, and dichloromethane was added to dissolve the solid. Then, n-hexane was added for recrystallization, and solid compound D was obtained by filtration.

[0057] 1.0 equivalent of D was dissolved in an appropriate amount of THF, 6.0 equivalents of hydrochloric acid were added, and the reaction was heated under reflux for 1 h. Ethyl acetate / water was used for extraction. The organic phase was dried and filtered. The solvent was drained, and the solid was dissolved with an appropriate amount of dichloromethane. Hexane was added for recrystallization, and the ligand compound E was obtained by filtration.

[0058] (2) General method for complex synthesis

[0059] Under anhydrous and oxygen-free conditions, weigh 1.0 equivalent of MCl4 powder, add appropriate amount of toluene and stir evenly, cool to -35°C, weigh 1.0 equivalent of ligand E at the same time, add appropriate amount of toluene and stir evenly, then add to the toluene solution of MCl4, continue stirring at low temperature for 30 minutes, then slowly drip 4.0-4.5 equivalents of methylmagnesium bromide ether solution (preferably 4.4 equivalents) into the above system, react at low temperature for 1 hour, slowly warm to room temperature, continue to react for 1 hour at room temperature, use an oil pump to vacuum remove the toluene solvent, add appropriate amount of toluene to dissolve the complex, filter out insoluble matter, quickly stir the filtrate, add n-hexane dropwise thereto until precipitation is just produced, freeze to -25°C for about 2 hours, precipitate more white crystalline solids, filter to obtain a colorless crystalline metal complex, place it in a 60°C oil bath, vacuum pump for 3 hours to remove the solvent, and obtain complex F.

[0060] Specific implementation of the present invention The preparation of the [NOON] tetradentate ligand fourth subgroup metal complex of the present invention having the structure of formula (I) is carried out according to the above method, specifically involving the preparation of complex F1, complex F3, complex F7 and complex F9:

[0061]

[0062] Wherein, for complex F1, R1 = hydrogen, R2 = hydrogen, R3 = methyl, M = Ti, X = methyl;

[0063] For complex F3, R1 = methyl, R2 = hydrogen, R3 = hydrogen, M = Zr, X = methyl;

[0064] For complex F7, R1 = methyl, R2 = hydrogen, R3 = isopropyl, M = Hf, X = methyl;

[0065] For complex F9, R1 = hydrogen, R2 = tert-butyl, R3 = cyclohexyl, M = Hf, X = methyl;

[0066] The present invention will be further described below in conjunction with embodiments:

[0067] Example 1

[0068] The synthesis of complex F1 was carried out according to the following synthetic route:

[0069]

[0070] (1) Synthesis of ligand E1

[0071] Under anhydrous and oxygen-free conditions, weigh 10 mmol of compound A1, add an appropriate amount of THF to fully dissolve it, then add 11 mmol of NaH, react at room temperature for 2 hours, add 11 mmol of CH3OCH2Cl, filter the obtained mixture, spin-dry the filtrate, add dichloromethane and water for extraction, collect the organic phase, dry it over anhydrous magnesium sulfate, and spin-dry to obtain compound B1.

[0072] Under a nitrogen atmosphere, 6 mmol of compound B1 was weighed and dissolved in an appropriate amount of THF, and then 6.6 mmol of compound C1 was added. The mixture was reacted at room temperature for 3 h. After the reaction solution was spin-dried, dichloromethane was added to dissolve the solid, and then n-hexane was added for recrystallization. The solid compound D1 was obtained by filtration.

[0073] Weigh 2 mmol of compound D1 and dissolve it in an appropriate amount of THF. Add 12 mmol of hydrochloric acid and heat to reflux for 1 h. Use ethyl acetate / water for extraction. Dry the organic phase and filter it. Drain the solvent. Dissolve the solid with an appropriate amount of dichloromethane. Add n-hexane for recrystallization and filter it to obtain the ligand compound E1.

[0074] (2) Synthesis of complex F1

[0075] Under anhydrous and oxygen-free conditions, weigh 10 mmol of TiCl4 powder, add an appropriate amount of toluene and stir evenly, cool to -35°C, weigh 10 mmol of the ligand compound E1, add an appropriate amount of toluene and stir evenly, then add to the toluene solution of TiCl4, continue stirring at low temperature for 30 minutes, then slowly drop 44 mmol of methyl magnesium bromide ether solution into the above system, react at low temperature for 1 hour, slowly warm to room temperature, continue to react at room temperature for 1 hour, use an oil pump to vacuum remove the toluene solvent, add toluene to dissolve the ligand The insoluble matter was removed by filtration, the filtrate was stirred rapidly, n-hexane was added dropwise thereto until precipitation was just formed, and the filtrate was frozen to -25°C for about 2 hours. A large amount of white crystalline solid was precipitated, which was filtered to obtain a colorless crystalline metal complex. The complex was placed in an oil bath at 60°C and vacuumed for 3 hours to remove the solvent to obtain 2.48g of complex F1, with a yield of 52.8%. The theoretical value of elemental analysis was: C, 63.84; H, 6.43; N, 5.96; the measured value of elemental analysis was: C: 63.72; H: 6.63; N: 5.56.

[0076] Example 2

[0077] The synthesis of complex F3 was carried out according to the following synthetic route:

[0078]

[0079] (1) Synthesis of ligand E3:

[0080] Under anhydrous and oxygen-free conditions, weigh 10 mmol of compound A3, add an appropriate amount of THF to fully dissolve it, then add 11 mmol of NaH, react at room temperature for 2 hours, add 11 mmol of CH3OCH2Cl, filter the obtained mixture, spin-dry the filtrate, add dichloromethane and water to extract, collect the organic phase, dry it over anhydrous magnesium sulfate, and spin-dry to obtain compound B3.

[0081] Under a nitrogen atmosphere, 6 mmol of compound B3 was weighed and dissolved in an appropriate amount of THF, and then 6.6 mmol of compound C3 was added. The mixture was reacted at room temperature for 3 h. After the reaction solution was spin-dried, dichloromethane was added to dissolve the solid, and then n-hexane was added for recrystallization. The solid compound D3 was obtained by filtration.

[0082] Weigh 2 mmol of compound D3 and dissolve it in an appropriate amount of THF, add 12 mmol of hydrochloric acid, heat and reflux to react for 1 h, use ethyl acetate / water for extraction, dry the organic phase and filter it, drain the solvent, dissolve the solid with an appropriate amount of dichloromethane, add n-hexane for recrystallization, and filter to obtain the ligand compound E3.

[0083] (2) Synthesis of complex F3

[0084] Under anhydrous and oxygen-free conditions, weigh 10 mmol of ZrCl4 powder, add appropriate amount of toluene and stir evenly, cool to -35°C, weigh 10 mmol of ligand compound E3 at the same time, add appropriate amount of toluene and stir evenly, then add to the toluene solution of HfCl4, continue stirring at low temperature for 30 minutes, then slowly drop 44 mmol of methyl magnesium bromide ether solution into the above system, react at low temperature for 1 hour, slowly warm to room temperature, continue to react for 1 hour at room temperature, use an oil pump to vacuum remove the toluene solvent, add toluene to dissolve the complex, filter out insoluble matter, quickly stir the filtrate, add n-hexane dropwise thereto until precipitation is just produced, freeze to -25°C for about 2 hours, precipitate more white crystalline solids, filter to obtain colorless crystalline metal complex, place it in a 60°C oil bath, vacuum for 3 hours to remove the solvent, and obtain 3.40 g of complex F3, with a yield of 66.2%. Theoretical values ​​of elemental analysis: C, 58.45; H, 5.89; N, 5.45; measured values ​​of elemental analysis: C: 58.55; H: 5.76; N: 5.87.

[0085] Example 3

[0086] The synthesis of complex F7 was carried out according to the following synthetic route:

[0087]

[0088] (1) Synthesis of ligand E7:

[0089] Under anhydrous and oxygen-free conditions, weigh 10 mmol of compound A7, add an appropriate amount of THF to fully dissolve it, then add 11 mmol of NaH, react at room temperature for 2 hours, add 11 mmol of CH3OCH2Cl, filter the obtained mixture, spin-dry the filtrate, add dichloromethane and water to extract, collect the organic phase, dry it over anhydrous magnesium sulfate, and spin-dry to obtain compound B7.

[0090] Under a nitrogen atmosphere, 6 mmol of compound B7 was weighed and dissolved in an appropriate amount of THF, and then 6.6 mmol of compound C7 was added. The mixture was reacted at room temperature for 3 h. After the reaction solution was spin-dried, dichloromethane was added to dissolve the solid, and then n-hexane was added for recrystallization. The solid compound D7 was obtained by filtration.

[0091] Weigh 2 mmol of compound D7 and dissolve it in an appropriate amount of THF. Add 12 mmol of hydrochloric acid and heat to reflux for 1 h. Use ethyl acetate / water for extraction. Dry the organic phase and filter it. Drain the solvent. Dissolve the solid with an appropriate amount of dichloromethane. Add n-hexane for recrystallization and filter it to obtain the ligand compound E7.

[0092] (2) Synthesis of complex F7

[0093] Under anhydrous and oxygen-free conditions, weigh 10 mmol of HfCl4 powder, add an appropriate amount of toluene and stir evenly, cool to -35°C, weigh 10 mmol of the ligand compound E7, add an appropriate amount of toluene and stir evenly, then add to the toluene solution of HfCl4, continue stirring at low temperature for 30 minutes, then slowly drop 44 mmol of methyl magnesium bromide ether solution into the above system, react at low temperature for 1 hour, slowly warm to room temperature, continue to react at room temperature for 1 hour, use an oil pump to vacuum remove the toluene solvent, add toluene to dissolve the complex The insoluble matter was removed by filtration, the filtrate was stirred rapidly, n-hexane was added dropwise thereto until precipitation was just formed, and it was frozen to -25°C for about 2 hours. A large amount of white crystalline solid was precipitated, which was filtered to obtain a colorless crystalline metal complex. It was placed in an oil bath at 60°C and vacuumed for 3 hours to remove the solvent to obtain 3.41g of complex F7, with a yield of 49.8%. The theoretical value of elemental analysis was: C, 54.34; H, 6.18; N, 4.09; the measured value of elemental analysis was: C: 55.02; H: 6.27; N: 4.56.

[0094] Example 4

[0095] The complex F9 was synthesized according to the following synthetic route:

[0096]

[0097] (1) Synthesis of ligand E9:

[0098] Under anhydrous and oxygen-free conditions, weigh 10 mmol of compound A9, add an appropriate amount of THF to fully dissolve it, then add 11 mmol of NaH, react at room temperature for 2 hours, add 11 mmol of CH3OCH2Cl, filter the obtained mixture, spin-dry the filtrate, add dichloromethane and water to extract, collect the organic phase, dry it over anhydrous magnesium sulfate, and spin-dry to obtain compound B9.

[0099] Under a nitrogen atmosphere, 6 mmol of compound B9 was weighed and dissolved in an appropriate amount of THF, and then 6.6 mmol of compound C9 was added. The mixture was reacted at room temperature for 3 h. After the reaction solution was spin-dried, dichloromethane was added to dissolve the solid, and then n-hexane was added for recrystallization. The solid compound D9 was obtained by filtration.

[0100] Weigh 2 mmol of compound D9 and dissolve it in an appropriate amount of THF. Add 12 mmol of hydrochloric acid and heat to reflux for 1 h. Use ethyl acetate / water for extraction. Dry the organic phase and filter it. Drain the solvent. Dissolve the solid with an appropriate amount of dichloromethane. Add n-hexane for recrystallization and filter it to obtain the ligand compound E9.

[0101] (2) Synthesis of complex F9

[0102] Under anhydrous and oxygen-free conditions, weigh 10 mmol of HfCl4 powder, add an appropriate amount of toluene and stir evenly, cool to -35°C, weigh 10 mmol of the ligand compound E9, add an appropriate amount of toluene and stir evenly, then add to the toluene solution of HfCl4, continue stirring at low temperature for 30 minutes, then slowly drop 44 mmol of methyl magnesium bromide ether solution into the above system, react at low temperature for 1 hour, slowly warm to room temperature, continue to react at room temperature for 1 hour, use an oil pump to vacuum remove the toluene solvent, add toluene to dissolve the complex The insoluble matter was removed by filtration, the filtrate was stirred rapidly, n-hexane was added dropwise thereto until precipitation was just formed, and it was frozen to -25°C for about 2 hours. A large amount of white crystalline solid was precipitated, which was filtered to obtain a colorless crystalline metal complex. It was placed in an oil bath at 60°C and vacuumed for 3 hours to remove the solvent to obtain 4.08g of complex F9, with a yield of 45.9%. The theoretical value of elemental analysis: C, 55.31; H, 6.34; N, 3.15; the measured value of elemental analysis: C: 61.88; H: 7.18; N: 3.52.

[0103] Example 5

[0104] The 500mL autoclave was vacuum dried for 2h in advance, the autoclave temperature was adjusted to the polymerization temperature, the ethylene gas was set to 0.3MPa, 200mL of n-heptane and 70mL of 1-octene were added first, and then 0.5mmol of methylaluminoxane (MMAO) was added, the temperature in the autoclave was raised to 120°C, and the ethylene pressure was adjusted to 2.5MPa after the temperature was raised to 120°C, and 2μmol of the toluene solution of the main catalyst F3 was injected, and ethanol was added to quench after polymerization for 10min. After the pressure was released, the polymer was discharged from the bottom of the autoclave, and the obtained polymerization reaction liquid was poured into 500mL of ethanol, stirred to obtain a white solid, filtered, and dried in a vacuum oven to constant weight to obtain 6.46g of polymer. GPC tests the molecular weight and molecular weight distribution, and the 1-octene insertion rate is obtained by high-temperature carbon spectrum (see Table 1 for details).

[0105] Example 6

[0106] The main catalyst F3 was changed to F7, and the other conditions were consistent with those in Example 5. The polymerization results are shown in Table 1.

[0107] Example 7

[0108] The main catalyst F3 was changed to F9, and the other conditions were consistent with those in Example 5. The polymerization results are shown in Table 1.

[0109] Example 8

[0110] The methylaluminoxane (MMAO) was replaced with a triisobutylaluminum / triphenylcarbonium tetrakis(pentafluorophenyl)borate complex, wherein the triisobutylaluminum was 0.5 mmol and the triphenylcarbonium tetrakis(pentafluorophenyl)borate was 3 μmol. The other conditions were consistent with those in Example 5. The polymerization results are shown in Table 1.

[0111] Example 9

[0112] The methylaluminoxane (MMAO) was replaced with trioctyl aluminum / N,N-dioctadecyl methylammonium tetrakis(pentafluorophenyl)borate complex, wherein the trioctyl aluminum was 0.5 mmol and the N,N-dioctadecyl methylammonium tetrakis(pentafluorophenyl)borate was 3 μmol. The other conditions were consistent with those in Example 7. The polymerization results are shown in Table 1.

[0113] Example 10

[0114] The n-heptane was replaced by n-hexane, and the other conditions were consistent with those in Example 6. The polymerization results are shown in Table 1.

[0115] Embodiment 11

[0116] 70 mL of 1-octene was replaced by 60 mL of 1-hexene. Other conditions were the same as those in Example 5. The polymerization results are shown in Table 1.

[0117] Example 12

[0118] The polymerization temperature was changed from 120°C to 140°C, and the other conditions were consistent with those in Example 6. The polymerization results are shown in Table 1.

[0119] Example 13

[0120] The polymerization pressure was changed from 2.5 MPa to 3.5 MPa, and the other conditions were consistent with those in Example 6. The polymerization results are shown in Table 1.

[0121] Table 1 Ethylene / α-olefin copolymerization data

[0122]

[0123] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A [NOON] tetradentate ligand fourth subgroup metal complex, characterized in that: It has the structure of formula (I): Wherein, R1, R2 and R3 are independently hydrogen, halogen, C1-C 20 Alkyl, C1~C 20 Cycloalkyl, C1~C 10 Alkoxy, C1~C 10 perfluoroalkyl, phenyl or substituted phenyl; wherein R1, R2 and R3 are not C1 cycloalkyl or C2 cycloalkyl; Said X is halogen, methyl or benzyl; The M is a fourth subgroup transition metal.

2. The complex according to claim 1, characterized in that Said R1 and R2 are independently hydrogen, fluorine, chlorine, methyl, methoxy, trifluoromethyl, isopropyl, tert-butyl, phenyl, 3,5-dimethylphenyl or 3,5-di-tert-butylphenyl; The R3 is hydrogen, methyl, ethyl, isopropyl, tert-butyl, cyclohexyl or phenyl.

3. The complex according to claim 1, characterized in that Said X is chlorine, bromine or methyl; The M is titanium, zirconium or hafnium.

4. The complex according to claim 1, characterized in that The complex having the structure of formula (I) is specifically a complex having the structures shown in the following F1 to F10: F1: R1 = hydrogen, R2 = hydrogen, R3 = methyl, M = Ti, X = methyl; F2: R1 = hydrogen, R2 = methyl, R3 = ethyl, M = Ti, X = Cl; F3: R1 = methyl, R2 = hydrogen, R3 = hydrogen, M = Zr, X = methyl; F4: R1 = methyl, R2 = hydrogen, R3 = ethyl, M = Zr, X = methyl; F5: R1 = tert-butyl, R2 = methyl, R3 = isopropyl, M = Zr, X = Cl; F6: R1 = methyl, R2 = tert-butyl, R3 = cyclohexyl, M = Zr, X = methyl; F7: R1 = methyl, R2 = hydrogen, R3 = isopropyl, M = Hf, X = methyl; F8: R1 = methyl, R2 = hydrogen, R3 = ethyl, M = Hf, X = Cl; F9: R1 = hydrogen, R2 = tert-butyl, R3 = cyclohexyl, M = Hf, X = methyl; F10: R1 = methyl, R2 = methyl, R3 = cyclohexyl, M = Hf, X = Cl.

5. A catalyst for olefin polymerization, characterized in that It includes a main catalyst and a co-catalyst; The main catalyst comprises the [NOON] tetradentate ligand fourth sub-group metal complex as described in any one of claims 1 to 4.

6. The catalyst for olefin polymerization according to claim 5, characterized in that The co-catalyst is selected from one or more of modified or unmodified alkylaluminoxane, alkylaluminum, organic boron or organic borate.

7. The catalyst for olefin polymerization according to claim 6, characterized in that The co-catalyst is selected from one or more of methylaluminoxane, modified methylaluminoxane, triethylaluminum, triisobutylaluminum, trioctylaluminum, perfluorophenylboron, triphenylcarbonium tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate and N,N-dioctadecylmethylammonium tetrakis(pentafluorophenyl)borate.

8. The catalyst according to claim 6, characterized in that The molar ratio of the aluminum atoms in the co-catalyst, the boron atoms in the co-catalyst and the metal atoms in the main catalyst is (5-1000):0:1, or 0:(1-5):1, or (5-1000):(1-5):

1.

9. A method for preparing a polyolefin, characterized in that it comprises the following steps: polymerizing at least one of ethylene or α-olefin under the action of a catalyst to obtain a polyolefin; The catalyst comprises a main catalyst and a co-catalyst; the main catalyst comprises the [NOON] tetradentate ligand fourth sub-group metal complex as described in any one of claims 1 to 4.

10. The preparation method according to claim 9, characterized in that: The polymerization temperature is 50 to 150° C. The polymerization is carried out at a pressure of 0.1 to 5 MPa.

Citation Information

Patent Citations

  • Ethylene polymerization catalyst, preparation and application thereof

    CN101885793A

  • Non-metallocene tridentate binuclear titanium complex, preparation method and purpose thereof

    CN104211726A

  • [NOON] tetradentate ligand fourth subgroup metal complex and application thereof

    CN113321674A

  • [ONNO] tetradentate fourth subgroup metal complex as well as preparation method and application thereof

    CN113637029A